Perbandingan Performa Lentur Balok Beton Bertulang dengan Sambungan Lewatan dan Mekanis Tipe Clamp - Iman, Dimas; Jafar, Jafar (Universitas Semarang, 2024)
Reinforcement bars, or rebar, face length limitations, prompting the need for connection methods in construction. Techniques like overlapping splicing, welding, and mechanical clamping address this. This research investigates flexural performance in reinforced concrete beams, focusing on tensile reinforcement splice methods—overlapping and mechanical clamping with a clamp connection. Key aspects such as flexural moment, deflection, and crack patterns are evaluated through laboratory testing using a two-point loading method. Findings show that beams with overlapping splices outperform those with mechanical clamping, with nominal moments of 33.5 kNm and 32.31 kNm, and deflections of 69.37 mm and 49.02 mm, respectively. Crack patterns in both samples indicate failure at one-third of the beam span due to reinforcement splices at the midpoint, enhancing cross-sectional area. In conclusion, this research underscores the superior performance of overlapping splices in terms of nominal moment and deflection, offering valuable insights for optimizing reinforced concrete element performance in structural engineering.